Description of Armadillidium boalense sp. nov. from northern Spain, with remarks and a key of the genus in the Iberian Peninsula and the Balearic Islands (Isopoda: Oniscidea: Armadillidiidae) - Cifuentes, Julio; Robla, Jairo; Garcia, Lluc (Zootaxa, 2024)
A new woodlice species of the genus Armadillidium Brandt, 1831 is described and illustrated from Asturias (northern Iberian Peninsula). Armadillidium boalense sp. nov. is ascribed to the ‘pictum group’ and is characterized by its eusphaeric conglobation, duplocarinate-type cephalon and strong sexual differentiation of the seventh pair of male pereopods. Furthermore, its diagnostic characteristics and its affinities with the rest of species of this group are discussed. The main diagnostic characteristics of a sometimes-questioned species Armadillidium galiciense Schmölzer, 1955 are also commented and illustrated. To facilitate the separation of the current known Iberian species of Armadillidium, an updated identification key is provided, and some new distributional and ecological data of other Armadillidium species of the Asturian region are also included.